Electroplating and Ablative Laser Structuring of Elastomer Composites for Stretchable Multi-Layer and Multi-Material Electronic and Sensor Systems - Simon P. Stier; Holger Böse (Micromachines, 2021)
In this work we present the concept of electroplated conductive elastomers and ablative multi-layer and multi-material laser-assisted manufacturing to enable a largely automated, computer-aided manufacturing process of stretchable electronics and sensors. Therefore, the layers (conductive and non-conductive elastomers as well as metal layers for contacting) are first coated over the entire surface (doctor blade coating and electroplating) and then selectively removed with a CO2 or a fiber laser. These steps are repeated several times to achieve a multi-layer-structured design. Is it not only possible to adjust and improve the work previously carried out manually, but also completely new concepts such as fine through-plating between the layers to enable much more compact structures become possible. In addition, metallized areas allow the direct soldering of electronic components and thus a direct connection between conventional and stretchable electronics. As an exemplary application, we have used the process for manufacturing a thin and surface solderable pressure sensor with a silicone foam dielectric and a stretchable circuit board.